1994
DOI: 10.1080/10862969409547851
|View full text |Cite
|
Sign up to set email alerts
|

Including Both Time and Accuracy in Defining Text Search Efficiency

Abstract: Factors related to efficiency in a textbook search task were examined. Previous definitions of search efficiency have used time as the only index in defining efficiency. The present study used a definition that included both time and accuracy. One hundred and twenty-nine university students searched for answers to eight low-inference questions in an earth science textbook and were administered the verbal section of the Scholastic Aptitude Test. Time and accuracy involved distinct processes; accuracy was relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Consequently, the text selected will be read more carefully to find out if it definitely answers the question, which means careful global reading will then take place (by reference to the parts of the text selected and not to the whole text, as discussed above). Search reading is also addressed by other authors such as Dreher (1992), Guthrie and Kirsch (1987), Symons and Specht (1994), as well as Enright et al (2000) specifically in relation to English language reading examinations.…”
Section: Survey On Reading Strategies Used In Ieltsmentioning
confidence: 97%
“…Consequently, the text selected will be read more carefully to find out if it definitely answers the question, which means careful global reading will then take place (by reference to the parts of the text selected and not to the whole text, as discussed above). Search reading is also addressed by other authors such as Dreher (1992), Guthrie and Kirsch (1987), Symons and Specht (1994), as well as Enright et al (2000) specifically in relation to English language reading examinations.…”
Section: Survey On Reading Strategies Used In Ieltsmentioning
confidence: 97%
“…Dreher and Guthrie (1990) studied how high school students locate answers to specific questions in a computer-presented textbook chapter. The amount of time university students take to locate answers to questions in a textbook is positively correlated with indexes indicative of extraction inefficiency, such as reinspection of text pages and missing sought-after information (Symons & Specht, 1994). Dreher (1992) found that more than 55% of the students who had not located the correct answers to questions in a textbook chapter did not 2 SYMONS ET AL.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…Our model of reading-to-assess also extends to models of text search (e.g., Byrnes & Guthrie, 1992;Dreher, 1992;Dreher & Guthrie, 1990;Guthrie & Kirsch, 1987;Guthrie &Mosenthal, 1987;Guthrie et al, 1993;Symons & Specht, 1994) that emphasize the importance of goals, selectivity, and integration into knowledge of thé reader. Our study highlights two further characteristics that are crucial to the skilled performance of reading-to-assess tasks in professional life: the need for formulating judgments on what is being read besides the more well-known goal of acquiring knowledge, and the way in which reading goals are specified during reading in a continuous interaction between reader knowledge and text information.…”
Section: Discussionmentioning
confidence: 90%
“…Most reading-to-do studies have focused on textual features that may account for performance that is less than optimal. Reading to locate specific information has also received much attention (e.g., Byrnes & Guthrie, 1992;Dreher, 1992;Dreher & Guthrie, 1990;Guthrie & Kirsch, 1987;Guthrie & Mosenthal, 1987;Guthrie, Weber, & Kimmerly, 1993;Symons & Specht, 1994). This research has been guided by a process model consisting of five components: goal formulation, inspecting appropriate categories of information, sequencing the inspection, extracting details from the categories, and recycling to obtain an answer on the question posed (Guthrie & Mosenthal, 1987).…”
mentioning
confidence: 99%